2018
DOI: 10.1002/cphc.201800021
|View full text |Cite
|
Sign up to set email alerts
|

Copper Affects the Location of Zinc in Bimetallic Ion‐Exchanged Mordenite

Abstract: Bimetallic ion exchange on a zeolite often impacts its catalytic properties compared to its monometallic counterparts. Here, we address the synergistic effect of simultaneous copper and zinc ion exchange on mordenite (MOR), as found earlier for dimethyl ether (DME) carbonylation. Samples with various Cu/Zn ratios were characterized by diffuse-reflectance infrared Fourier-transform spectroscopy (DRIFTS) in the 3600 and 720 cm regions, pore distribution analysis through Ar physisorption, X-ray photoelectron spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The chemical principle is that transition metals have strong ability for CO adsorption and activation, which facilitates CO insertion into the methyl group adsorbed on a vicinal acid site of HMOR. Cu, Ni, Co, Zn modified HMOR catalysts, prepared either by impregnation or ion-exchange, showed higher activity or stability than the parent HMOR in DME carbonylation, with Cu as the most efficient promoter [38,44,[51][52][53][54][55][56][57][58] . Interestingly, co-addition of Cu and Zn to HMOR resulted in more dramatic improvement in both activity and stability as compared to the addition of either Cu or Zn individually.…”
Section: Dme Carbonylation Over Zeolitesmentioning
confidence: 98%
See 1 more Smart Citation
“…The chemical principle is that transition metals have strong ability for CO adsorption and activation, which facilitates CO insertion into the methyl group adsorbed on a vicinal acid site of HMOR. Cu, Ni, Co, Zn modified HMOR catalysts, prepared either by impregnation or ion-exchange, showed higher activity or stability than the parent HMOR in DME carbonylation, with Cu as the most efficient promoter [38,44,[51][52][53][54][55][56][57][58] . Interestingly, co-addition of Cu and Zn to HMOR resulted in more dramatic improvement in both activity and stability as compared to the addition of either Cu or Zn individually.…”
Section: Dme Carbonylation Over Zeolitesmentioning
confidence: 98%
“…A combined IR, UVvis and theoretical modeling study indicated that monometallic exchange of Cu and Zn resulted in their location at T1 and (T3 + T4) sites of HMOR framework, respectively; while Cu promoted the preferable location of Zn from T3 site to T4 site when they are co-exchanged. The enhanced stability of the Cu -Zn/HMOR catalyst was ascribed to block the T4 sites which was assumed to be responsible for the formation of coke precursor [56,57] . Introducing Fe into the framework T sites of HMOR, during the hydrothermal process, was also reported to enhance the catalytic activity, and especially stability, in DME carbonylation.…”
Section: Dme Carbonylation Over Zeolitesmentioning
confidence: 99%
“…Considering DME carbonylation, the existence of a synergic effect between Cu and Zn in the carbonylation reaction has been shown. Zn cations are preferentially located in T3 sites of the 8MR pockets, but exchanging H-MOR with Zn and Cu results in the presence of Cu in these sites while Zn 2+ is now located in the T4 sites of the 12MR pockets [232]. Finally, it should be mentioned that a similar mechanism has been proposed for the polyoxometalate-based catalysts, where methoxy groups adsorbed con acid sites react with cationic species that hold CO molecules [233].…”
Section: The Synthesis Of Acetic Acid Using Co 2 -Rich Feedstocksmentioning
confidence: 72%
“…In addition to single-metal modification, bimetal modification has also been investigated. Reule et al [36,37] used ion exchange-modified MOR with Cu and Zn and found that the addition of Zn effectively increased the dispersion of Cu, which affected the location of Zn in MOR during ion exchange. Catalyst poisoning was effectively alleviated by the interaction between Cu and Zn.…”
Section: Introductionmentioning
confidence: 99%